The Effectiveness of Distance Learning Assessment Practices: Case Study (International Journal of Scientific Research and Management (IJSRM), 2024)
Assessment is an essential component of the educational process as it tracks the progress of lessons, activities and facilitates learning through formative assessment or measures performance towards graduation or entry to higher levels of education or employment through summative assessment. However, increasing student enrollments in open-access educational institutions and the need for frequent assessments have led to a shift towards ICT (information and communication technologies) based remote assessment methods. The emergence of health emergencies and the strategy of Moroccan higher education has further accelerated this transition from traditional in-person assessments to remote assessments. This study uses a transversal research design to analyze the impact of distance assessment practices at Sultan Moulay Slimane University in Morocco. The research method includes the development of a benchmark for distance education evaluation methods and a statistical survey of randomly selected students (293) in eight university establishments, as well as other stakeholders involved in the remote assessment process. The objective is to determine the evaluation methodologies most appropriate to the specific context of Sultan Moulay Slimane University. Data is analyzed using descriptive statistics.